Feasibility analysis procedures for public projects in Iceland - Hafliði Richard Jónsson 1967- (2012)
Investment decisions for public projects in Iceland have often been controversial and it is not always clear how prioritization and selection of projects is evaluated. Icelandic law on public project arrangement, however, requires the opposite, whereas it requires that different solutions to achieve the defined need must be examined and compared internally before applying for funding. One of the few products of this work according to this law shall be a feasibility analysis used for comparison. Requirements for conducting feasibility analysis, however, are not further defined in this law or referred to for further definitions. This thesis determines and defines what factors and/or attributes must be analysed in the feasibility analysis process as well as what procedures can be classified as best practises when performing feasibility analysis during the conception phase of public projects in Iceland. The main objective of this thesis is to benchmark current practises within the official sector in Iceland against best practises and recommend changes if necessary. This thesis includes a qualitative case study of initial reports on six construction projects in Iceland: Vaðlaheiði tunnel, Landeyjar port, Harpa Reykjavík concert hall and conference centre, Upper secondary school in Mosfellsbær, Avalanche protection in Bolungarvík and Snæfellsstofa visitor centre in Vatnajökull national park. The result shows that the current methodology of performing feasibility analysis during the conception phase of public projects in Iceland varies considerably. There does not seem to be much consistency in procedures and there are only a few incidents that can be determined according to best practice. Fjárfestingarákvarðanir í tengslum við opinberar framkvæmdir á Íslandi hafa oft á tíðum verið umdeildar og ekki hefur alltaf verið ljóst hvernig forgangsröðun og val á verkefnum hefur farið fram. Lög um skipan opinberra framkvæmda krefjast þó hins gagnstæða, en þau fara fram á að framkvæmd sé könnun og samanburður þeirra kosta er ...